Alcohol and the risk of pneumonia: a systematic review and meta-analysis - Simou, Evangelia; Britton, John; Leonardi-Bee, Jo (BMJ Publishing Group Ltd, 2018)
Objective: A systematic review and meta-analysis to estimate the magnitude of the association between alcohol consumption and the risk of community acquired pneumonia (CAP) in adults was undertaken. Design: Systematic review and meta-analysis Methods: Comprehensive searches of Medline, EMBASE and Web of Science were carried out to identify comparative studies of the association between alcohol intake and CAP between 1985 and 2017. Reference lists were also screened. A random effects meta-analysis was used to estimate pooled effect sizes. A dose response meta-analysis was also performed. Results: We found 17 papers eligible for inclusion in the review, of which 14 provided results which could be pooled. Meta-analysis of these 14 studies identified a 83% increased risk of CAP among people who consumed alcohol, or in higher amounts, relative to those who consumed no, or lower amounts of alcohol respectively (RR= 1.83, 95% CI: 1.30-2.57). There was substantial between-study heterogeneity, which was attributable in part to differences in study continent, adjustment for confounders, and pneumonia diagnosis (clinical vs death). Dose-response analysis found that for every 10-20 grams higher alcohol intake per day, there was 8% increase in the risk of CAP. Conclusions: The findings suggest that alcohol consumption increases the risk of CAP. Therefore, strengthening policies to reduce alcohol intake would be likely to reduce the incidence of CAP.